A fotografia cultural e a religação das culturas: um estudo sob o prisma do pensamento complexo. - Vieira, Nancely Huminhick (2012)
The aim of this thesis is to understand how the Cultural Photography stands before the subject, which is complex, and how it adapts to different cultures as those imposed by imprinting. Intends to offer arguments to show that this subject is expressed by means of photography in a subjective way. The theoretical framework focuses on the complexity theory, Edgar Morin and different spectra of the photography are guided mainly by Boris Kossoy. On in one hand the complex thinking contributes to the rewiring of cultures and understanding of homo complexus, on the other, the various questions of photography bring out different ways to rethink it, in order to be able to bring out a new concept of photography the Cultural Photography which is inserted in the social context, economic and political of contemporary societies. In the brief course of history of photography, some pictorial icons are highlighted in relation to the complexity, as well as the photographic language, the core of the subject-photographer in emerging cultural imprinting the baggage the cultural filter of the photographer in choosing and composition of his photography creations. Following are presented and analyzed different photographic genres, such as: Photography Journalism, Photography Documentaries and Photography Anthropological. The goal is to point out similarities and differences between genres, in order to establish relations with sources and Cultural Photography. Art and Science are subjects to discuss from definitions of humanistic and scientific culture and its relationship and linkages with photography. In this research, carried out by the findings, we present our concept of Cultural Photography and is through the images and analyses we made on them that exemplify our object betting on a non-verbal language.